Value of regional myocardial flow measurements using Rubidium-82 PET. (20th July 2021) - Koenders, SS; Van Dalen, JA; Jager, PL; Mouden, M; Slump, CH; Van Dijk, JD
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The combination of myocardial blood flow (MBF) measurements using Rubidium-82 (Rb-82) PET and visual assessment of the PET images is increasingly used due to its high diagnostic and prognostic value. Typically, flow measurements are calculated and used for the myocardium as a whole (global). However, small regional flow deficits may go unnoticed when only looking at global flow values. Purpose: To compare the diagnostic value of regional and global myocardial flow measurements using Rb-82 PET in the detection of obstructive CAD. Methods: We retrospectively included 1034 patients with no history of coronary artery disease (CAD) referred for rest and regadenoson-induced stress Rb-82 PET/CT. MBFs were calculated using Lortie's one-tissue compartment model. Myocardial flow reserve (MFR) was calculated as the ratio of MBF during stress and rest. Regional flow was determined per vessel and per segment. Vessel MFR was defined as the lowest flow reserve of LAD, LCX and RCA territories and segmental MFR as the lowest flow reserve in all 17 segments. Follow-up data were obtained from medical records. Patients were classified to have obstructive CAD if follow-up included a positive invasive coronary angiography (ICA), percutaneous coronary intervention (PCI), coronary artery bypass grafting (CABG) or all cause death. Receiver-operating characteristic (ROC) analyses were constructed to compare the diagnostic value of global and regional flow values. Results: Follow-up was obtained in all 1034 patients and the median follow-up time was 2.1 years. Myocardial flow reserve values were significantly lower (p < 0.001) in the 128 patients classified with obstructive CAD than in the 906 patients without obstructive CAD: global MFR (median 1.9 [interquartile range 1.6-2.4] vs. 2.5 [2.1-2.9]); vessel MFR (1.6 [1.3-2.1] vs. 2.3 [1.9-2.6]); Segmental MFR (1.3 [0.9-1.7] vs. 1.9 [1.6-2.2]). The area under the curve of vessel MFR (0.79 ± 0.02) and segmental MFR (0.81 ± 0.02) were similar but significantly (p < 0.001) larger than the area of global MFR (0.75 ± 0.03), as shown in the Figure. Conclusion: The diagnostic value improved with the use of regional MFR instead of global MFR measurements in the detection of obstructive CAD. Therefore, it seems that visual assessment of PET images can best be combined with regional flow measurements either on a per vessel or a per segment basis in Rubidium-82 PET myocardial perfusion imaging.